Why Are Single-Sex Schools Successful? - Christian Dustmann; Hyejin Ku; Do Wan Kwak (Center for Economic Studies and ifo Institute (CESifo), 2017)
We exploit two unusual policy features of academic high schools in Seoul, South Korea—random assignment of pupils to high schools within districts and conversion of some existing single-sex schools to the coeducational (coed) type over time—to identify three distinct causal parameters: the between-school effect of attending a coed (versus a single-sex) school; the within-school effect of school-type conversion, conditional on (unobserved) school characteristics; and the effect of class-level exposure to mixed-gender (versus same-sex) peers. We find robust evidence that pupils in single-sex schools outperform their counterparts in coed schools, which could be due to single-sex peers in school and classroom, or unobservable school-level covariates. Focusing on switching schools, we find that the conversion of the pupil gender type from single-sex to coed leads to worse academic outcomes for both boys and girls, conditional on school fixed effects and time-varying observables. While for boys, the negative effect is largely driven by exposure to mixed-gender peers at school-level, it is class-level exposure to mixed-gender peers that explains this disadvantage for girls.
Keywords: I20; J16; 330; gender; single sex schools; school inputs; random assignment